Geospatial Analysis of Marine Habitat Representation for Marine Spatial Planning Around Waiheke Island Auckland New Zealand - Murdoch-Tighe, Levi (Auckland University of Technology, 2022)
This thesis compares differences in marine habitat composition for different sections of coast within 1 km of Waiheke Island located in the inner Hauraki Gulf, Auckland, New Zealand (36.800° S, 175.101° E). The maps, graphs, multivariate analyses and Marxan simulated annealing models developed consistently identify distinct differences in habitat composition among sections of coast and provide options for a representative and adequate network of complementary MPAs which include a range of habitats and associated biodiversity. Four distinct groups of marine habitats required adequate representation in protected areas, but their distribution was limited to a relatively small number of locations. The groups were: the intertidal and subtidal boulder and gravel habitats found mainly off north-western Waiheke Island and in the Nani-Onetangi and the Pie Melon-Te Whau sections of coast; high current habitats in the Motutapu and Waiheke Island Channels; seagrass, mangrove, saltmarsh and mud flat habitats in the Rocky-Pūtiki, Kennedy-Huruhi, Awaawaroa Bay and Te Matuku Bay Marine Reserve; and the deep gravel, mud and other habitats of the Horuhoru (Gannet Rock) to Hooks Bay section of coast. There is, however, flexibility to choose areas that include other biodiversity values and also provide for social, economic and cultural values and activities. Establishing MPAs in these locations would complement customary management and other fisheries, conservation and land management practices to help restore and protect ecosystems around the island and also contribute to objectives for the Hauraki Gulf Marine Park and national marine spatial planning. The resulting GIS models can be used in participatory management with scientists, stakeholders, iwi and the public to help plan and assess conservation actions around Waiheke Island and in the surrounding Marine Park.
Keywords: Marine protected area; Reserve; GIS; Marxan, marine spatial planning